HIV multi-drug resistance at first-line antiretroviral failure and subsequent virological response in Asia - Awachana Jiamsakul (2018)
Introduction: First-line antiretroviral therapy (ART) failure often results from the development of resistance-associated mutations (RAMs). Three patterns, including thymidine analogue mutations (TAMs), 69 Insertion (69Ins) and the Q151M complex, are associated with resistance to multiple-nucleoside reverse transcriptase inhibitors (NRTIs) and may compromise treatment options for second-line ART. Methods: We investigated patterns and factors associated with multi-NRTI RAMs at first-line failure in patients from The TREAT Asia Studies to Evaluate Resistance - Monitoring study (TASER-M), and evaluated their impact on virological responses at 12 months after switching to second-line ART. RAMs were compared with the IAS-USA 2013 mutations list. We defined multi-NRTI RAMs as the presence of either Q151M; 69Ins; ≥ TAMs; or M184V+ ≥ 1 TAM. Virological suppression was defined as viral load (VL) < 400 copies/ml at 12 months from switch to second-line. Logistic regression was used to analyze (1) factors associated with multi-NRTI RAMs at first-line failure and (2) factors associated with virological suppression after 12 months on second-line. Results: A total of 105 patients from 10 sites in Thailand, Hong Kong, Indonesia, Malaysia and Philippines were included. There were 97/105 (92%) patients harbouring ≥1 RAMs at first-line failure, 39/105 with multi-NRTI RAMs: six with Q151M; 24 with ≥2 TAMs; and 32 with M184V+ ≥1 TAM. Factors associated with multi-NRTI RAMs were CD4 ≤200 cells/μL at genotyping (OR = 4.43, 95% CI [1.59-12.37], p = 0.004) and ART duration > 2 years (OR = 6.25, 95% CI [2.39-16.36], p < 0.001). Among 87/105 patients with available VL at 12 months after switch to second-line ART, virological suppression was achieved in 85%. The median genotypic susceptibility score (GSS) for the second-line regimen was 2.00. Patients with ART adherence ≥95% were more likely to be virologically suppressed (OR = 9.33, 95% CI (2.43-35.81), p = 0.001). Measures of patient resistance to second-line ART, including the GSS, were not significantly associated with virological outcome. Conclusions: Multi-NRTI RAMs at first-line failure were associated with low CD4 level and longer duration of ART. With many patients switching to highly susceptible regimens, good adherence was still crucial in achieving virological response. This emphasizes the importance of continued adherence counselling well into second-line therapy. © 2014 Jiamsakul A et al; licensee International AIDS Society.